MITIGATING CLIMATE CHANGE IN QURANIC PERSPECTIVE : (A STUDY OF THEMATIC INTERPRETATION IN A SCIENTIFIC APPROACH) - Nur Fitriani Syam,; Sulkifli,; Muhammad Yunan, (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2025)
The objective of this study is to reveal the Mitigation of Climate Change from the Perspective of the Qur'an. To demonstrate the meaning of climate change mitigation in the Qur'an, the author employs a thematic interpretation method with a scientific approach to study the verses of the Qur'an related to the causative factors (fasad) and efforts in overcoming climate change. This research is qualitative. The results of this study reveal that mitigation or efforts that can be made to overcome climate change are (1) increasing faith and piety in Allah, the almighty God, so that humans can control their lusts. With the ability to control lust, human activities are only intended to prosper, stem damage and persecution, and improve the quality of life. (2) Increasing environmental awareness and conducting sustainable management.